2000
DOI: 10.1007/s004240000338
|View full text |Cite
|
Sign up to set email alerts
|

Volume-sensitive KCl cotransport associated with human cervical carcinogenesis

Abstract: This study investigates the volume-sensitive KCI cotransporter (KCC) in various types of human cervical epithelial cell, testing the hypothesis that cervical malignancy is accompanied by differential expression of volume-sensitive KCC. Normal human cervical epithelial cells have KCCs which are quiescent in normal physiological conditions and are relatively refractory to hypotonic stress. By contrast, cervical cancer cells have KCCs which are also nearly quiescent in normal physiological conditions but high tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 24 publications
2
74
0
Order By: Relevance
“…Our previous studies suggested that the swelling-activated KCC works in concert with ion channels to mediate regulatory volume decrease of cervical cancer cells (8,9). Prompted by the observation of substantially increased swelling-activated KCC by IGF-1, we tested the hypothesis that IGF-1 might similarly enhance cell volume regulation.…”
Section: Igf-1 Stimulated Kcc Activity and Enhanced Kcc-dependent Cellmentioning
confidence: 98%
See 3 more Smart Citations
“…Our previous studies suggested that the swelling-activated KCC works in concert with ion channels to mediate regulatory volume decrease of cervical cancer cells (8,9). Prompted by the observation of substantially increased swelling-activated KCC by IGF-1, we tested the hypothesis that IGF-1 might similarly enhance cell volume regulation.…”
Section: Igf-1 Stimulated Kcc Activity and Enhanced Kcc-dependent Cellmentioning
confidence: 98%
“…Functional K ϩ ( 86 Rb ϩ ) Efflux Assays-Unidirectional K ϩ efflux was carried out at 37°C as described in detail elsewhere (7,8). In brief, cells were preincubated with isotonic culture medium loaded with 2 Ci/ml 86 Rb ϩ for 2 h at 37°C.…”
Section: Cell Cultures and Creation Of Kcc Mutant Cell Lines-mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the fact that the suppressions of RVD were greater in Cl − -free and high-K + solutions (53 and 44%, respectively) than those obtained with individual Cl − and K + channel inhibitors (27% and 27%, respectively), suggests the existence of a heterogeneous family of volume-sensitive ion transients mechanisms, only some of which are sensitive to NA and 4-AP (Nilius et al, 1996). KCl cotransporter (KCC) is another type of contributor to RVD, which has been described in multiple cell lines, including HCEC and RCEC (Capo-Aponte et al, 2005, 2007aErnest et al, 2005;Lauf and Adragna, 2000;Shen et al, 2000;Wehner et al, 2003). The contribution of this alternative mechanism to RVD is variable in different species, but less than that mediated by Cl − and K + channel activity.…”
Section: Discussionmentioning
confidence: 99%